MEL scripting for Maya animators - Wilkins, Mark R.; Kazmier, Chris; Osterburg, Stephan; ScienceDirect eBooks (Amsterdam ; Boston : Morgan Kaufmann, 2005)
MEL scripting for Maya animators, 2nd edition, includes new features, such as a discussion of global procedures, new chapters on fixing programming bottlenecks, advanced user interface techniques, and optimizing character rigs. New chapters on utility nodes and Maya's Web Panel feature provide new ideas on how to use MEL in applications--Resource description page.
Preface; Special Acknowledgment; Chapter 1 Maya Under the Hood; Chapter 2 The Basics of MEL Commands; Chapter 3 Using Expressions; Chapter 4 Controlling Particles with Expressions; Chapter 5 Problem Solving with MEL Scripting; Chapter 6 Variables and Data Types; Chapter 7 Using MEL Commands; Chapter 8 Manipulating Nodes in MEL; Chapter 9 Controlling the Flow of Execution; Chapter 10 Procedures and Functions; Chapter 11 Naming Nodes, Scripts, and Variables; Chapter 12 Designing MEL User Interfaces; Chapter 14 Custom Dialog Boxes; Chapter 15 Making Advanced Dialog Boxes with form Layout; Chapter 16 Making Advanced Dialog Boxes with Web Panels; Chapter 17 Improving Performance With Utility Nodes; Chapter 18 Installing MEL Scripts; Chapter 19 Examples Using MEL with Particle Dynamics; Chapter 20 Examples Using MEL with Solid Body Dynamics; Chapter 21 Example of a Simple Crowd System; Chapter 22 Examples Using MEL in Character Rigging; Index.
Includes index.
Print version record.
Safari Books Online
Elsevier
Keywords: Maya (Computer file); Maya (Computer file); Maya (Computer file); Computer animation; Computer graphics; COMPUTERS -- Digital Media -- Video & Animation; Computer animation; Computer graphics; Computer animation; Computer graphics; Electronic books